The effect of Fe substitution on pyroelectric properties of 0.62Pb(Mg1/3Nb2/3)O-3-0.38PbTiO(3) single crystals - Chew, Khian Hooi; Luo, H.S.; Wan, X.M.; Chan, H.L.W.; Choy, C.L.; Zhao, X.Y. (2005)
Fe-doped 0.62Pb(Mg1/3Nb2/3)O-3-0.38PbTiO(3) (PMN-0.38PT) single crystals with two different dopant concentrations, 0.2 and 1.0 mol %, were grown by a modified Bridgman technique. The effect of Fe substitution on dielectric and pyroelectric properties was examined. The dielectric constant of the 0.2 mol % Fe-doped PMN-0.38PT single crystal was controlled successfully, indicating the possibility of tuning the dielectric properties by doping with a small concentration of iron ions. The mechanism of doping effect was also discussed based on the principles of crystal chemistry. The pyroelectric response of the single crystals was measured using a dynamic method from 20 to 50 degrees C. Compared with the 1.0 mol % Fe-doped single crystal, the 0.2 mol % Fe-doped sample possesses the better pyroelectric properties. At room temperature, the pyroelectric coefficient and detectivity figure of merit (F-D) for the 0.2 mol % Fe-doped sample are 568 mu C/m(2) K and 53 mu Pa-1/2, respectively, and they increase slightly with temperature increasing. These excellent pyroelectric properties as well as being able to produce large-size and high-quality single crystals make this kind of single crystal a promising candidate for high-performance infrared detectors and other pyroelectric applications. (C) 2005 American Institute of Physics.